Seismic Retrofitting and Health Monitoring of School Buildings of Cyprus - Chrysostomou, Christis; Kyriakides, Nicholas; Kappos, A.J.; Demetriou Georgiou, E.; Millis, M.; Kouris, L. (My University, 2013)
The vulnerability of existing buildings to seismic forces and their retrofitting is an international problem. The majority of structures in seismic-prone areas worldwide are structures that have been designed either without the consideration of seismic forces, or with previous codes of practice specifying lower levels of seismic forces. In Cyprus, after the three earthquakes that occurred in 1995, 1996, and 1999, the Cyprus State, acting in a pioneering way internationally, has decided the seismic retrofitting of all school buildings, taking into account the sensitivity of the society towards these structures, which house the future generation of the society. In this paper the overall assessment methodology is presented, along with details of the over 10 year ongoing retrofitting program of the school buildings of Cyprus, with emphasis on the description of the program and the development of a wireless monitoring system. In addition, mathematical models of selected school buildings are presented and comparison is made with in-situ measurement.
Keywords: Seismic retrofitting; Schools; Health monitoring; Existing structures